Trends in Bicycle Accidents and Injury Analysis in Poland: Insights from 2016 to 2023 - Sebastian Glowinski; Szymon Rzepczyk; Maciej Obst (Safety, 2025)
Bicycle safety remains a critical concern as cycling gains popularity, especially in urban areas where traffic conditions pose significant risks. The increasing presence of bicycles and derivatives of them further complicates traffic dynamics, raising the potential for accidents and injuries. This study examines bicycle accident trends in Poland from 2016 to 2023 using data provided by the Polish Police, supplemented with medical insights on injury mechanisms. The analysis highlights key patterns, such as the higher incidence of accidents during summer, fewer accidents on weekends compared to weekdays, and the disproportionate fatality rate among cyclists over 60. Failure to yield the right of way emerges as a leading cause of accidents. These findings underscore the need for a multifaceted approach to improving cyclist safety, including infrastructural enhancements, public education, stricter enforcement of traffic laws, and advancements in medical response and protective gear. Addressing these factors can contribute to a safer environment that supports the continued growth of sustainable and active transportation.